Decision Making In a Higher Educational Organization: a Literature Review - Tiara Nove Ria; Desi Surlitasari Dewi (Majalah Ilmiah Inspiratif, 2022)
A manager's position requires him or her to make decisions. This is a critical task, particularly for managers who are in charge of planning. Educational institutions, whether in Kindergarten, Elementary School, Junior High School, Senior High School or even High School or University, are organized institutions which also need a manager as the leader. The purpose of this article is to explore the decision making in educational organization that can be applied in the higher educational environment. This conceptual article is developed based on several literature review. There are 14 articles were reviewed in order to get the notion of decision making, the elements that influence decision making, and the efficacy of decision making and problem solving so that can be implemented in higher educational institutions. As a conclusion, decision-making in the field of higher education, particularly for educational leaders in higher educational organization, must be able to choose the best option alternatives so that educational institutions' organizational goals of enhancing performance and quality of education can be met ideally.Keywords: decision making, higher education, educational organization